Pastorale implikasies van die liggaam/denke verbintenis - Coetzer, Wentzel Christoffel (Verbum et ecclesia, 2006)
Against the background of the body/mind connection the focus is firstly on the Biblical view of man as an unfragmented unity. Secondly the emphasis is on the historical roots of the so called biopsychosocial model that is replacing the traditional biophysical method. Furthermore, the focus is also placed on the possibility of physical problems as the result of unresolved emotions; the immune system as an important link within the body/mind connection; critical life changes; the role of genetics as well as important decisions of the will; social support and loneliness; and, the therapeutical value of writing or verbalization. In conclusion the emphasis is put on the pastoral implications of all the above mentioned factors and a plea is made for the inclusion of the pastoral/spiritual dimension in the biospychosocial model. This will lead to a fully multidisciplinary approach in the counseling of the traumatized and/or emotionally wounded person.